Biomaterials - Biological Engineering Society ([IPC Science and Technology Press], 1980)
"Biomaterials is an international journal covering the science and application of biomaterials and associated medical devices. It is the aim of the journal to provide a peer-reviewed forum for the publication of original papers and authoritative review papers dealing with the most important issues facing the use of materials in clinical practice. The scope of the journal covers the basic science and engineering aspects of biomaterials, including their mechanical, physical, chemical and biological properties, relevant design and production characteristics of devices constructed of these materials, and their clinical performance. In this context, biomaterials are defined as all those materials used in medical devices in which contact with the tissues of the patient is an important and guiding feature of their use and performance. They include a range of metals and alloys, glasses and ceramics, natural synthetics, polymers, biomimetics, composites and natural or tissue-derived materials, including combinations of synthetic materials and living tissue components. The journal is relevant to all applications of biomaterials including implantable medical devices, tissue engineering and drug delivery systems."
Keywords: Biomedical materials : Periodicals; Biomedical materials; Biocompatible Materials; Biocompatible Materials : Periodicals; Biocompatible Materials : periodicals; Biomatériaux : Périodiques; Biomatériaux; Bioengineering materials : Periodicals